Transcriptome Analysis of Jujube (Ziziphus jujuba Mill.) Response to Heat Stress - Lei Yang; Juan Jin; Dingyu Fan; Qing Hao; Jianxin Niu (International Journal of Genomics)
Heat stress (HS) is a common stress influencing the growth and reproduction of plant species. Jujube (Ziziphus jujuba Mill.) is an economically important tree with strong abiotic stress resistance, but the molecular mechanism of its response to HS remains elusive. In this study, we subjected seedlings of Z. jujuba cultivar “Hqing1-HR” to HS (45°C) for 0, 1, 3, 5, and 7 days, respectively, and collected the leaf samples (HR0, HR1, HR3, HR5, and HR7) accordingly. Fifteen cDNA libraries from leaves were constructed for transcriptomics assays. RNA sequencing and transcriptomics identified 1,642, 4,080, 5,160, and 2,119 differentially expressed genes (DEGs) in comparisons of HR1 vs. HR0, HR3 vs. HR0, HR5 vs. HR0, and HR7 vs. HR0, respectively. Gene ontology analyses of the DEGs from these comparisons revealed enrichment in a series of biological processes involved in stress responses, photosynthesis, and metabolism, suggesting that lowering or upregulating expression of these genes might play important roles in the response to HS. This study contributed to our understanding of the molecular mechanism of jujube response to HS and will be beneficial for developing jujube cultivars with improved heat resistance.